Effect of feeding whole soybean and linseed on milk and parmigiano reggiano cheese lipid fraction - Mordenti, Attilio Luigi; Brogna, Nico; Merendi, Flavia; Canestrari, Giorgia; Dall'Olio, Massimo; Biagi, Giacomo; Formigoni, Andrea (Progress in Nutrition, 2015)
Aim of this study was to assess the effects of feeding whole soybean flakes and whole extruded linseed to dairy cows on milk lipid fraction and Parmigiano Reggiano cheese produced from it; specifically, PUFA and CLA contents were evaluated. For 14 weeks, a herd of 145 cows received a diet with a daily supplementation of 1 kg of whole soybean flakes and 0.3 kg of whole extruded linseed. In the pre-trial period, cows received an isoproteic ration devoid of both seeds. From 20 cows selected from the herd, individual milk, bulk morning milk and vat milk samples of the entire herd were taken every 14 days. After 24 months of aging, cheese samples were taken from twelve cheese wheels, obtained from milk produced at 0, 4, 8, 10, 12 and 14 weeks on the same days as bulk milk and vat milk samples were made. Fatty acid composition of the lipid fraction was determined in all milk and cheese samples. Feeding whole extruded linseed and soybean flakes has determined a decrease in short-chain fatty acids content and an increase in total CLA concentration of the milk. Bulk milk, vat milk and aged cheese analysis samples confirmed a decrease of short-chain fatty acids content in milk and revealed a decrease in n-6/n-3 fatty acid and in saturated/unsaturated fatty acid ratios. In conclusion, feeding a ration including whole soybean flakes and extruded linseed can improve the nutritional characteristics of milk and of Parmigiano Reggiano cheese, particularly with respect to their lipid fractions.